Homozygotes for HbE and Anaemia -3 Years Study in Rajshahi - Khan, MR; Shah, MS Uddin; Aziz, MA; Khan, MMR; Rahman, M Khalilur; Khanam, Khadiza (TAJ: Journal of Teachers Association, 2011)
HbE is the most common abnormal hemoglobin of Southeast Asia and is almost limited to this region. It is estimated that 30 million people are heterozygous for HbE and that 1 million are homozygous. Aim of this study was to know the number of homozygous for haemoglobin E condition (Hb E disease) patients among patients suspected of having hereditary haemoglobin disorders referred to the regional laboratory, in Rajshahi. From April 2009 to March 2012, anaemic patients suspected of having hereditary haemoglobin disorder (haemoglobinopathy or thalassemia) were referred to the divisional laboratory, Rajshahi for hemoglobin electrophoresis from the physicians of different areas of Rajshahi division and part of Khulna division. Patient’s age ranging from 01 to 85 yrs of both sexes. Two to three milliliter blood was collected in tubes containing EDTA for complete blood count (CBC) and analysis of hemoglobin variants. CBC was measured by the Erma PC 604 particle counter. Peripheral blood film were examined after staining with Wright’s stain.9 Hemoglobin electrophoresis was carried out on cellulose acetate using TEB buffer, pH 8.6.9. Of 707 anaemic patients suspected of having hereditary haemoglobin disorder (haemoglobinopathy or thalassemia) 333 (47%) were abnormal. Of this abnormal patients 35 (11%) revealed a thalassemia-like disorder, 53 ( 17%) patients revealed haemglobin E disease, 46 ( 14%) patients haemglobin E trait and 188 ( 57%) patients having double heterozygous (Hb E/β thalassemia) disorder. The birth incidence for homozygous babies and or Eβ thalassemia would be increases per year. Population groups with higher frequencies require screening programmes and facilities for antenatal diagnosis. Future comprehensive study are require to know the actual prevalence. TAJ 2011; 24(1): 34-37